Flight training changes the brain functional pattern in cadets - Chen, Xi; Wang, Zian; Jiang, Hao; Meng, Yu; Wang, Hongmei; Li, You; Xu, Kaijun; Yang, Jiazhong; Luo, Cheng (Frontiers in Neuroscience, 2023)
To our knowledge, this is the first study to use MRI (Magnetic Resonance Imaging) before and after an intensive flight training. This study aimed to investigate the effectiveness of flight training in civil flying cadets. The civil flying cadets and controls completed two study visits. Visit 1 was performed in 2019, and high spatial resolution structural image and resting-state functional MRI data were collected. The second visit was completed in 2022. In addition to the MRI data mentioned above, participants completed the cognitive function assessment at the second visit. Mixed-effect regression model analysis found that flight training enhanced the degree centrality (DC) values of the left middle frontal gyrus and left lingual gyrus. The subsequent correlation calculation analysis suggested a possible relationship between these alterations and cognitive function.